PENGOLAHAN AIR PAYAU MENJADI AIR BERSIH MENGGUNAKAN METODE ELEKTROKOAGULASI - Kaslum, Leila; ., Fadarina; Meidinariasty, Anerasari; Yuliati, Selastia; Syakdani, Adi; Pratama, M.Bagas; Alpitansyah, Rachmad Bayu; Alnafrah, Fenty; Ismareni, Pepi (KINETIKA, 2021)
The limitation of clean water resources in coastal areas is related to the scarcity of fresh water. Water that has too high a salinity can cause harm if it is used for certain activities, for example, it is dangerous for health when used as drinking water, causing crop failure for agriculture, corrosion for equipment and buildings made of metal elements. In order to be used as clean water and suitable for daily household use, brackish water needs special treatment with the aim of reducing the mineral content in it, especially in reducing salinity levels. For this purpose brackish water treatment has been made into clean water which works based on the electrocoagulation process. The performance test was carried out by filling 10 liters of brackish water into the electrocoagulation reactor and using an electric current of 10 volts, 12 volts and 14 volts for each test. The observation times for each test were 60, 120 and 180 minutes. Measurement of salinity, iron, sulfate and organic substances for each test was carried out using a potentiometer, atomic absorption spectrophotometer, turbidimeter, and titrimetry. The optimum results of the test show that the use of 14 volts of electricity and contact time for 120 minutes can reduce iron levels from 1.41 mg / l to 0.98 mg / l, and sulfate levels from 301.97 mg / l to 235.84 mg. / l, levels of organic substances from 3.05 mg / l to 2.25 mg / l and salinity levels from 16.25 ppt to 10.07 ppt.